Advances in the study of the correlation between balanoposthitis and skin microecology - Wang, Mingyue; Gao, Xinghua; Zhang, Li (Frontiers in Microbiology, 2025)
Balanoposthitis is a common heterogeneous skin condition involving the glans penis and prepuce, and is seen from infancy to old age. Its predisposing factors are intertrigo, lengthy foreskin, localized irritation, and mucosal injury. The itching and skin inflammation at the glans penis seriously affects the quality of life of patients. As a result of advances in high-throughput sequencing technology, the prepuce microbial colonization patterns and glans penis are now known better. Previous studies have shown that an imbalance of flora can cause balanoposthitis. This article summarizes the progress of research on balanoposthitis and skin microecology, and provides a direction for the subsequent exploration of immunological mechanisms in balanoposthitis.